2022
DOI: 10.3389/fphys.2022.924908
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Blood Flow Autoregulation in Offspring From Experimentally Preeclamptic Rats and the Effect of Age

Abstract: Preeclampsia is a hypertensive disorder of pregnancy that causes significant, long term cardiovascular effects for both the mother and offspring. A previous study demonstrated that middle cerebral arteries in offspring from an experimental rat model of preeclampsia were smaller, stiffer, and did not enlarge over the course of maturation, suggesting potential hemodynamic alterations in these offspring. Here we investigated the effect of experimental preeclampsia on cerebral blood flow autoregulation in juvenile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 88 publications
1
2
0
Order By: Relevance
“…This may explain our previous findings of reduced cerebral blood flow observed in the motor and somatosensory cortex of P5-PELS. 10 Furthermore, these findings agree with previous reports 12,13 showing impaired brain vascular function in both the middle cerebral artery and vein of Galen after birth (postnatal days 16–30) in offspring from PELS. Nevertheless, our results contrast with another study in adult offspring (12 months of age) of PELS generated in transgenic female mice overexpressing human angiotensinogen and renin, which showed increased cerebral blood flow in response to whisker stimulation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This may explain our previous findings of reduced cerebral blood flow observed in the motor and somatosensory cortex of P5-PELS. 10 Furthermore, these findings agree with previous reports 12,13 showing impaired brain vascular function in both the middle cerebral artery and vein of Galen after birth (postnatal days 16–30) in offspring from PELS. Nevertheless, our results contrast with another study in adult offspring (12 months of age) of PELS generated in transgenic female mice overexpressing human angiotensinogen and renin, which showed increased cerebral blood flow in response to whisker stimulation.…”
Section: Discussionsupporting
confidence: 91%
“…11 Animal studies have also shown defects in the structure and function of the middle cerebral artery in offspring from rat preeclampsia-like syndrome (PELS) model. 12,13 More recently, we found that mice (postnatal day 5 [P5]) of PELS (characterized by a reduction in placental perfusion) showed a significant decrease in brain perfusion, which may involve structural alterations in the brain microcirculation. 10 Vascular endothelial growth factor (VEGF), placental growth factor (PlGF), and VEGF receptors (VEGFRs) are critical regulators of angiogenesis.…”
mentioning
confidence: 99%
“…In rats most of literatures investigated the changes in the uterine blood flow during different models either for diabetes [27,28], preeclampsia [29,30] or the intrauterine fetal growth retardations [30][31][32][33]. Accordingly, the results of the present study regarding the investigation of uterine blood flow changes during normal pregnancy in rats would be considered as a references values for the uterine arteries Doppler indexes variation.…”
Section: Discussionmentioning
confidence: 90%